Parsing the Hypomanic Personality: Explicating the Nature of Specific Dimensions Defining Mania Risk. (April 2019) - Stanton, Kasey; McArtor, Daniel B.; Watson, David
Considerable research has used the Hypomanic Personality Scale (HPS) to assess traits conferring risk for hypomanic and manic episodes. Although the HPS has been shown to be defined by several distinct sets of content, most research has continued to rely exclusively on HPS total scores, due to (a) little research having examined its structure and (b) the discrepant structural results obtained in the few available studies. Therefore, we examined the structure and relations of the HPS in a large sample of community adults ( N = 737) receiving psychiatric treatment. Our structural results indicated a five-factor structure of Activation, Charisma, Intellectual Confidence, Lability, and Modesty. Subscales modeling these emergent factors showed divergent patterns of relations with personality and other forms of psychopathology. These findings underscore the importance of examining HPS subscale relations in addition to HPS total scores in future research.